Long-Term Trends in Unintentional Fall Mortality in China: A Population-Based Age-Period-Cohort Study - Wang, Zhenkun; Hu, Youzhen; Peng, Fang (Frontiers in Public Health, 2021)
Background: Unintentional falls seriously threaten people's life and health in China. This study aims to assess the long-term trends of mortality from unintentional falls in China and to examine the age-, period-, and cohort-specific effects behind them. Methods: This population-based multiyear cross-sectional study of Chinese people aged 0 to 84 years was a secondary analysis of the mortality data of falls injury from 1990 to 2019, derived from the Global Burden of Disease Study 2019. Age-standardized mortality rates of unintentional falls by year, sex, and age group were used as the main outcomes and were analyzed within the age-period-cohort framework. Results: Although the crude mortality rates of unintentional falls for men and women showed a significant upward trend, the age-standardized mortality rates for both sexes only increased slightly. The net drift of unintentional falls mortality was 0.13% (95% CI, −0.04% to 0.30%) per year for men and -0.71% (95% CI, -0.96% to -0.46%) per year for women. The local drift values for both sexes increased with age group. Significant age, cohort, and period effects were found behind the mortality trends of the unintentional falls for both sexes in China. Conclusions: Unintentional falls are still a major public health problem that disproportionately threatens the lives of men to women in China. Efforts should be put in place urgently to prevent the growing number of fall-related mortality for men over 40 years old and women over 70 years old. Gains observed in recent period RRs and cohort RRs may be related to improved healthcare and better education.